Effectiveness of Metformin Monotherapy vs. Metformin-Insulin Combination on Glycemic Control for Type 2 Diabetes in Eastern Libya - Adnan Asheibi; Amhidi, Ahmed; Hamza Alasbily; Hwuida Maghoud; Ghada Hadiia (AlQalam Journal of Medical and Applied Sciences, 2025)
Type 2 diabetes (T2D) management focuses on achieving optimal glycemic control to mitigate the risk of complications. Metformin monotherapy and metformin-insulin combination therapy are standard treatment approaches. This study aimed to compare the efficacy of metformin monotherapy versus metformin combined with insulin in achieving glycemic control in T2D patients in Eastern Libya. A cross-sectional study was conducted from July 1, 2023, to December 30, 2023, involving 226 participants out of an initial 239, after applying inclusion and exclusion criteria. Eligible participants included T2D patients on metformin monotherapy or combination therapy, aged 18 years and older, with a minimum treatment duration of three months. Exclusion criteria included those on other regimens or newly diagnosed. The final sample consisted of 43.4% males (n=98) and 56.6% females (n=128), with a mean age of 58 years, mean disease duration of 12.9 years, and a mean HbA1c of 7.7%. Of the participants, 91 were on metformin monotherapy, which demonstrated a lower mean HbA1c of 7.1% (±0.93), compared to the 128 participants on metformin-insulin combination therapy, with a mean HbA1c of 8.1% (±1.1). An independent T-test revealed a statistically significant difference (p<0.001). These findings suggest that metformin monotherapy may be more effective in achieving glycemic control in certain T2D patients. Future studies are warranted to validate these results and further investigate potential influencing factors. يعتمد علاج مرض السكري من النوع الثاني على التحكم في مستويات السكر في الدم لمنع المضاعفات. يعد العلاج الأحادي بالميتفورمين و العلاج المركب الجامع بين الميتفورمين مع الأنسولين من الأساليب العلاجية الشائعة. هدفت هذه الدراسة إلى مقارنة الفاعلية بين العلاج الأحادي بالميتفورمين مقارنةً مع العلاج المركب في تحقيق السيطرة على نسبة السكر في الدم من خلال قياس مستويات الهيموغلوبين السكري. اعتمدت هذه الدراسة تصميمًا مقطعيًا، حيثُ تم تضمين 226 من أصل 239 مشاركًا في التحليل النهائي، تم تجنيدهم من مركز بنغازي لتشخيص و علاج السكري، و مركز الجبل الأخضرللسكري، وعيادة شحات في الفترة من 1 يوليو 2023 إلى 30 ديسمبر 2023. استبعدت الدراسة المشاركين الذين تقل أعمارهم عن 18 عامًا، و المشخصين حديثًا، و أولئك الذين يتبعون نظامًا علاجيًا غير العلاج اللأحادي بالميتوفرمين أو العلاج المركب، والذين تقل مدة استخدامهم للعلاج عن 3 أشهر. تكونت عينة الدراسة النهائية من 43.4% من الذكور و 56.6% من الإناث بمتوسط عمر 58 عامًا، و متوسط مدة الإصابة بالسكري من النوع الثاني 12.9 سنة، و متوسط هيموغلوبين سكري قدره 7.7%. بلغ عدد المشاركين الذين يتلقون العلاج الأحادي 91 مشارك و اظهروا متوسط هيموغلوبين سكري أقل حيث بلغ 7.1% (± 0.93)، مقارنة بالعلاج المركب الذي شمل 128 مشاركًا بمتوسط هيموغلوبين سكري 8.1% (± 1.1). تم إستخدام اختبار (ت) لعينتين مستقلتين، مما أظهر أن الفرق الملاحظ كان ذا دلالة إحصائية. تشير هذه النتائج إلى أن العلاج الأحادي بالميتفورمين قد يوفر تحكمًا أفضل على مستويات السكر في الدم لدى بعض مرضى السكري من النوع الثاني. يُوصى بإجراء المزيد من الدراسات لتأكيد هذه النتائج واستكشاف العوامل المؤثرة